“Efecto de la fertilización orgánica e inorgánica en el cultivo de maíz (Zea mays) en la Parroquia Puerto Limón, Provincia de Santo Domingo de los Tsáchilas”. - Intriago Peñarrieta, Ingrid Nicole (2022)
This research was carried out in the parish of Puerto Limón in the canton of Santo Domingo de Tsáchilas, with the objective of evaluating the effect of organic and inorganic fertilizers on corn (Zea mays). An experimental design of completely randomized blocks (DCRB) was used, with 5 treatments and 4 repetitions, in factorial arrangement (AxB), where factor A was the sources or fertilizers and factor B the dose of applications according to the demand of the silver, resulting in the following treatments: T1: Organic F. at 100%, T2: Organic F. at 50%, T3: Inorganic F. at 100% T3: Inorganic F. at 50% and T5 Witness. The best results were obtained in T3: greater plant height at 15, 30 and 60 days with 30.27, 64.35 and 197 centimeters, as well as greater stem diameter 6.22, 12.18 and 38.88 mm; 12.18 and 38.88 mm, best ear with a weight of 390 gr, length 25 cm, width 71.25 mm, 16 rows of grains, 330 grains, best weight of 100 grains 33.38 gr, estimated yield with the highest field moisture 6878.13, best yield adjusted to 13% moisture, 5296.37 kg equivalent to 116.40 metric quintals (100 pounds), therefore the most profitable with 39.48%, although financially speaking no treatment is viable because it has a B/C ratio of less than 1. On the other hand, T5 was the earliest flowering treatment, flowering at 55, 38 days on average, in addition to grain as the lowest moisture 39%. Demonstrating the positive effect of inorganic fertilizers applied in doses that cover 100% of plant demand.